The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0104-11692012000600013
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Intervention Classifications (NIC) validated for patients at risk of pressure ulcers

Abstract: Objective: to validate the Nursing Intervention Classifications (NIC) for the diagnosis 'Risk of Impaired Skin Integrity' in patients at risk of pressure ulcers (PU). Method: the sample comprised 16 expert nurses. The data was collected with an instrument about the interventions and their definitions were scored on a Likert scale by the experts. The data was analyzed statistically, using the calculation of weighted averages (WA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 7 publications
1
23
0
4
Order By: Relevance
“…Within the NDs of NANDA-I (19) , it is understood that the Risk for impaired skin integrity is the one that better describes the patients' condition at PU risk, subsidizing the better lesion preventive care planning although it is not the more specific for this type of worsening (12) . For its better accuracy, the Braden Scale risk assessment instrument can be used (12)(13)(14)19,23) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Within the NDs of NANDA-I (19) , it is understood that the Risk for impaired skin integrity is the one that better describes the patients' condition at PU risk, subsidizing the better lesion preventive care planning although it is not the more specific for this type of worsening (12) . For its better accuracy, the Braden Scale risk assessment instrument can be used (12)(13)(14)19,23) .…”
Section: Discussionmentioning
confidence: 99%
“…For its better accuracy, the Braden Scale risk assessment instrument can be used (12)(13)(14)19,23) . The prescribed cares to patients with this ND were majorly related to the PU prevention, for example to protect skin to avoid rupture, to moisturize skin, to inspect skin searching for hyperemic or ischemic points.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Systematic reviews of some predictive scales with various lists of risk factors can be found in Bóriková (2006) and Fúrová (2006). The foreign literature refers to substantially more scales for prediction of pressure ulcers; some authors have attempted to modify the existing scales (Lepistӧ et al, 2006;Pancorbo-Hidalgo et al, 2006;Bavaresco, Lucena, 2012;Hyun et al, 2014;Demarre et al, 2015;Kumari et al, 2015). The nursing diagnosis of at Risk of Pressure Ulcers 00249 was included in the international classification of nursing diagnoses, NANDA International for 2015-2017, as a potentially new nursing diagnosis in Domain 11 Safety/Protection -a Class 2 Physical Injury (NANDA International, 2014).…”
Section: Introductionmentioning
confidence: 99%